Karel van Mander and his Foundation of the Noble, Free Art of Painting: First English Translation, with Introduction and Commentary - Melion, Walter S (Brill, 2022)
Written by the poet-painter Karel van Mander, who finished it in June 1603, the Grondt der edel, vry schilderconst (Foundation of the Noble, Free Art of Painting) was the first systematic treatise on schilderconst (the art of painting / picturing) to be published in Dutch (Haarlem: Paschier van Wes[t]busch, 1604). This English-language edition of the Grondt, accompanied by an introductory monograph and a full critical apparatus, provides unprecedented access to Van Mander’s crucially important art treatise. The book sheds light on key terms and critical categories such as schilder, manier, uyt zijn selven doen, welstandt, leven and gheest, and wel schilderen, and both exemplifies and explicates the author’s distinctive views on the complementary forms and functions of history and landscape.